Patient-reported Outcomes and Burden of Disease in Paediatric Patients with Psoriasis: Real-world Data from EU5 and US - Marieke M.B. Seyger; Amy Paller; Michael Sticherling; Teresa Bachhuber; Nicolas Thomas; James Hetherington; James Lucas; Craig Richardson; Matthias Augustin (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)